Toko Oli Social Media Business Strategy Planning - Kelvin Hendra Lim; Renny Christiarini (Universitas Internasional Batam, 2023)
Toko Oli is a business that sells oil products for two and four-wheeled vehicles, besides selling oil products, the owner also provides oil change services. The problem faced by Toko Oli is that from time to time there is a day when there is not a single consumer at Toko Oli. The method used is by conducting interviews and documentation to obtain information and materials needed to implement digital marketing strategies. The solution provided is by utilizing social media to reach new consumers and using Google maps to provide information and layouts that are easily obtained by consumers. The results of the application of social media, namely, managed to reach 34,375 audiences, with 22,837 engagements on Toko Oli Facebook Business and Instagram, the owner said there were consumers who came because of social media and as for consumers who contacted the owner regarding services and products at Toko Oli. Next community service is then recommended to adjust social media that is often used by the community so that it can reach more consumers.